Remittances and Institutions : Are Remittances a Curse? - Dagher, Jihad; Abdih, Yasser; Chami, Ralph; Montiel, Peter (Washington, D.C. : International Monetary Fund, 2008)
This paper addresses the complex and overlooked relationship between the receipt of workers' remittances and institutional quality in the recipient country. Using a simple model, we show how an increase in remittance inflows can lead to deterioration of institutional quality - specifically, to an increase in the share of funds diverted by the government for its own purposes. Empirical testing of this proposition is complicated by the likelihood of reverse causality. In a cross section of 111 countries we document a negative impact of the ratio of remittance inflows to GDP on domestic institutional quality, even after controlling for potential reverse causality. We find that a higher ratio of remittances to GDP is associated with lower indices of control of corruption, government effectiveness, and rule of law.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet